Gas sensing properties of p-type hollow NiO hemispheres prepared by polymeric colloidal templating method - Cho, Nam Gyu; Hwang, In-Sung; Kim, Ho-Gi; Lee, Jong-Heun; Kim, Il-Doo (ELSEVIER SCIENCE SA, 2011)
This work presents a simple and versatile route to produce macroporous p-type metal oxide thin films. Two-dimensional arrays of p-type NiO films with a hollow hemisphere structure were fabricated by colloidal templating and RF-sputtering followed by a subsequent heat treatment. The diameter and shell thickness of the NiO hemisphere were 800 nm and 20 nm, respectively. X-ray diffraction and high-resolution transmission electron microscopy analysis indicate that the pure NiO phase with grain size of 10 nm was obtained at calcination temperatures that exceeded 450 degrees C. Close-packed arrays of hollow NiO hemispheres were found to exhibit p-type gas sensing properties against (CO, H-2, C3H8, CH4, NO2, and C2H5OH), leading to significantly enhanced responses to C2H5OH (R-gas/R-air = 5.0 at 200 ppm). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: SENSITIVITY